2020
DOI: 10.1073/pnas.1917770117
|View full text |Cite
|
Sign up to set email alerts
|

Structural cavities are critical to balancing stability and activity of a membrane-integral enzyme

Abstract: Packing interaction is a critical driving force in the folding of helical membrane proteins. Despite the importance, packing defects (i.e., cavities including voids, pockets, and pores) are prevalent in membrane-integral enzymes, channels, transporters, and receptors, playing essential roles in function. Then, a question arises regarding how the two competing requirements, packing for stability vs. cavities for function, are reconciled in membrane protein structures. Here, using the intramembrane protease GlpG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…Another aspect in the structural analysis of protein communities should be toward membrane interactions and membrane-associated complexes. Other works have shown that various protein community members require either close proximity to a membrane structure (Sanders and Hutchison, 2018) or to be embedded into one in order to perform their function (Guo et al, 2020). For the aforementioned reasons, membrane mimetics can be added to a fractionated sample with the goal of recovering such interactions for subsequent cryo-EM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect in the structural analysis of protein communities should be toward membrane interactions and membrane-associated complexes. Other works have shown that various protein community members require either close proximity to a membrane structure (Sanders and Hutchison, 2018) or to be embedded into one in order to perform their function (Guo et al, 2020). For the aforementioned reasons, membrane mimetics can be added to a fractionated sample with the goal of recovering such interactions for subsequent cryo-EM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ser442 was predicted to be located in an intramembrane region. Studies have shown that these regions often have a special role in the protein stability and function [ 46 , 47 ]. Results of Gly472Arg variant revealed that arginine is a charged and hydrophilic residue compared to wildtype.…”
Section: Resultsmentioning
confidence: 99%
“…With this arrangement, streptavidin concentration can effectively force unfolding. This method has successfully been used to study the thermodynamics of folding and unfolding within natural bilayers and bicelles (bilayer-like disks; Hong et al, 2010;Hong & Bowie, 2011;Chang & Bowie, 2014;Nadeau et al, 2015;Guo et al, 2016Guo et al, , 2020. In theory, a method to rapidly remove the biotin tags would allow for kinetic studies of refolding.…”
Section: Second Stage Folding Pathways In Bilayersmentioning
confidence: 99%